Peculiarities of development of inflorescences and flowering of purple coneflower (Echinacea purpurea (L.) Moench) and pale coneflower (Echinacea pallida (Nutt.) Nutt.) in the foreststeppe of Ukraine - Поспєлов, С. В. (Scientific Progress & Innovations, 2012)
The peculiarity of flowering of purple coneflower (Echinacea purpurea (L.) Moench) cultivar «Zirka Mykoly Vavilova» (Star of Nikolai Vavilov) and pale coneflower Echinacea pallida (Nutt.) Nutt.) variety «Krasunya preriy» (Prairie’s Beauty) in the foreststeppe of Ukraine have been studied. For the first time according to many years’ data in a production environment it has been established that the inflorescences formation of purple coneflower begins in May, massive flowering – in July. One plant per season forms 48.2 inflorescence with the mass of 184.25 g. The period of flowering inflorescence of the first-order lasts an average for 34 days, other orders – 33–43 days. One plant blooms up to 65 days. Pale coneflower begins the formation of inflorescences in May, a massive bloom – in June. The plant per a season forms 10.4 inflorescence with the mass of 30.1 g. Inflorescence of the firstorder flowers up to 15 days, other orders – 19–29 days. The total period of flowering plants lasts for 34–37 days. Research of biological peculiarities of flowering should be considered in the design of medical, food and melliferous agrocenosis of Echinacea. Also at that time of planning harvesting the surface mass for medicinal raw materials, regulating the efficiency and duration of flowering.